1985
DOI: 10.1111/j.1467-1770.1985.tb01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Tense Marking: A Case for the Obvious

Abstract: The recent focus on the discourse level as the primary basis for explaining alternation in interlanguage tense marking is challenged on the basis of an analysis of tense marking for 16 Vietnamese speakers learning English as a second language. The subjects represent four different age levels (10–12, 15–18, 20–25, and 35–55) and two different length of residency groups (1–3 and 4–7 years). The analysis reveals that there are a number of surface‐level constraints that systematically affect the incidence of tense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 17 publications
6
94
0
2
Order By: Relevance
“…Thus, while making less use of the inflected form, Group 1 extends this form to an almost similar range of verbs as Group 2. We do not find any difference for regular and irregular verbs, such that irregularly inflected forms might emerge before regularly inflected ones, as reported by Bayley (1996) and Dietrich et al (1995) for the acquisition of past time morphology (see also Wolfram's 1985 Principle of Perceptual Salience which suggests that the saliency surrounding irregular morphology favours its earlier acquisition compared to regular morphological forms). In the case of the periphrastic form, we also note that, in spite of its differential use across the groups, both Groups 2 and 3 extend this form to a very limited range of lexical verbs, at just 4 and 2 respectively.…”
Section: Arborescences Revue D'études Françaises Issn: 1925-5357 112supporting
confidence: 63%
“…Thus, while making less use of the inflected form, Group 1 extends this form to an almost similar range of verbs as Group 2. We do not find any difference for regular and irregular verbs, such that irregularly inflected forms might emerge before regularly inflected ones, as reported by Bayley (1996) and Dietrich et al (1995) for the acquisition of past time morphology (see also Wolfram's 1985 Principle of Perceptual Salience which suggests that the saliency surrounding irregular morphology favours its earlier acquisition compared to regular morphological forms). In the case of the periphrastic form, we also note that, in spite of its differential use across the groups, both Groups 2 and 3 extend this form to a very limited range of lexical verbs, at just 4 and 2 respectively.…”
Section: Arborescences Revue D'études Françaises Issn: 1925-5357 112supporting
confidence: 63%
“…The regular forms are much simpler and more straightforward than the irregular ones in that only a suffix '-ed' is attached at the end of a word. It is found that the regular past is used more inconsistently than the irregular past (Wolfram, 1985 andBayley, 1994 as cited in Solt et al, 2004). Celce-Murcia, Brinton, and Goodwin (1996) propose that students whose first language has more restricted final consonant clusters than English frequently pronounce every '-ed' endings as fully syllabic [ɪd] or [əd] owing to lacking knowledge of past tense marking phonological rules.…”
Section: Introductionmentioning
confidence: 99%
“…Regularization may be a beneficial strategy when the variability in the observed forms is not conditioned on a previous linguistic context. Unpredictable variation of this sort is not commonly found in most languages, at least in the speech of native speakers (e.g., Chambers et al, 2003); however, it is much more common when learning from non-native speakers (Wolfram, 1985;Johnson et al, 1996). In such circumstances, when the input is truly inconsistent, regularization can be beneficial.…”
Section: Introductionmentioning
confidence: 99%